Pengaruh Fasilitas dan Harga terhadap Kepuasan Pengunjung (Study Kasus pada Camp Kobes) - Halim, Jane Jovita (Universitas Darwan Ali, 2023)
This study aims to analyze the effect of facilities and prices on visitor satisfaction (Camp Kobes Case Study). This type of research is Quantitative and sample collection techniques using non-probability sampling methods through a convenience sampling approach and 100 people as a sample. The analysis data uses multiple regression. The results of the study partially showed that the facilities did not have a significant effect on visitor satisfaction. And the price partially has a significant effect on visitor satisfaction. This means that the more affordable the price, the more satisfied visitors are.